Genome-Wide Identification, Genomic Organization, and Characterization of Potassium Transport-Related Genes in Cajanus cajan and Their Role in Abiotic Stress - Muhammad Hussnain Siddique (MDPI AG, 2021)
Potassium is the most important and abundant inorganic cation in plants and it can comprise up to 10% of a plant’s dry weight. Plants possess complex systems of transporters and channels for the transport of K+ from soil to numerous parts of plants. Cajanus cajan is cultivated in different regions of the world as an economical source of carbohydrates, fiber, proteins, and fodder for animals. In the current study, 39 K+ transport genes were identified in C. cajan, including 25 K+ transporters (17 carrier-like K+ transporters (KUP/HAK/KTs), 2 high-affinity potassium transporters (HKTs), and 6 K+ efflux transporters (KEAs) and 14 K+ channels (9 shakers and 5 tandem-pore K+ channels (TPKs). Chromosomal mapping indicated that these genes were randomly distributed among 10 chromosomes. A comparative phylogenetic analysis including protein sequences from Glycine max, Arabidopsis thaliana, Oryza sativa, Medicago truncatula Cicer arietinum, and C. cajan suggested vital conservation of K+ transport genes. Gene structure analysis showed that the intron/exon organization of K+ transporter and channel genes is highly conserved in a family-specific manner. In the promoter region, many cis-regulatory elements were identified related to abiotic stress, suggesting their role in abiotic stress response. Abiotic stresses (salt, heat, and drought) adversely affect chlorophyll, carotenoids contents, and total soluble proteins. Furthermore, the activities of catalase, superoxide, and peroxidase were altered in C. cajan leaves under applied stresses. Expression analysis (RNA-seq data and quantitative real-time PCR) revealed that several K+ transport genes were expressed in abiotic stress-responsive manners. The present study provides an in-depth understanding of K+ transport system genes in C. cajan and serves as a basis for further characterization of these genes.